A Load Balance Routing Algorithm Based on Uneven Clustering - Liang Yuan; Chuan Cai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Aiming at the problem of uneven load in clustering Wireless Sensor Network (WSN), a kind of load balance routing algorithm based on uneven clustering is proposed to do uneven clustering and calculate optimal number of clustering. This algorithm prevents the number of common node under some certain cluster head from being too large which leads load to be overweight to death through even node clustering. It constructs evaluation function which can better reflect residual energy distribution of nodes and at the same time constructs routing evaluation function between cluster heads which uses MATLAB to do simulation on the performance of this algorithm. Simulation result shows that the routing established by this algorithm effectively improves network’s energy balance and lengthens the life cycle of network. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3403